Erratic Behavioral Attitude Leads to Noncommunicable Diseases: A Cross-Sectional Study. (10th January 2020) - Habib, Arif; Alam, Mohammad Mahtab; Hussain, Izhar; Nasir, Nazim; Almuthebi, Musa
Abstract : Background . The burden of noncommunicable diseases (NCDs) in the Arab world has reached an alarming level. Behavioral risk factors including consumption of fast food, inadequate sleep, and skipping meals are pervasive. This study aims at establishing the association between NCDs and modernized behavioral risk factors among populations. Methods . A cross-sectional study was carried out with 1070 respondents who were 18 years old. The data were collected using a structured questionnaire with the help of the WHO STEPS approach with some modifications regarding NCD risk factors. Results . 30% of respondents had cardiovascular diseases (CVD) followed by respiratory diseases (23%) and diabetes (3%) while the habit of smoking was found among 52% of respondents followed by physical inactivity (49%), skipping meals (24%), and inadequate sleep (30%). Consumption of fast food was found to be a significant risk factor for obesity (odds ratio (OR) = 2.72, 95% confidence interval (CI) [1.50, 4.92]), CVD (OR = 1.52, 95% CI [1.20, 1.94]), and respiratory disease (OR = 2.13, 95% CI [1.58, 2.86]). Significant linkages were found between CVD and smoking (OR = 0.69, 95% CI [0.54, 0.88]), diet pattern (OR = 1.86, 95% CI [1.44, 2.39]), fast food (OR = 1.52, 95% CI [1.20, 1.94]), and sleep hours (OR = 0.57, 95% CI [0.42, 0.79]). Conclusions . Undesirable behavioral risk factors pose a considerable threat to public health with a high prevalence rate of NCDs. Reducing the NCD burden and promoting healthy lifestyle formation of suitable strategies and their smooth implementation is the need of the hour.